Relato sobre o Projeto Pintura na Fachada, idealizado por uma professora - artista e seus desdobramentos reflexivos - Leme, Mariana Soares (2018)
This artistic work / teaching has as public youths in public schools of basic educa¬tion, promoting rapprochement between the school and community through artistic action, ie, paintings on the walls of the houses of the resi¬dents, bringing out new forms of relationships between those involved directly and indirectly in the Facade Painting Project